2007
DOI: 10.1515/jpem.2007.20.8.853
|View full text |Cite
|
Sign up to set email alerts
|

McCune-Albright Syndrome and Disorders Due to Activating Mutations of GNAS1

Abstract: It has been more than seven decades since Drs. Fuller Albright and Donovan McCune published the first reports on individuals with McCune-Albright syndrome (MAS). Since then, the classic triad of precocious puberty, café-aulait spots, and polyostotic bone dysplasia continues to define the syndrome. However, having gathered a better picture of the pathophysiology of MAS, the way this condition is understood has changed. Isolated activating mutations of the alpha subunit of the G protein (GNAS1) have been found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 152 publications
0
36
1
Order By: Relevance
“…7 -11 Adrenocortical hyperplasia in the presence of a partially inactivated PDE is likely to be caused by high cellular cAMP levels in a manner analogous to endocrine tumor formation in McCune -Albright syndrome. 7,12 The GWA study identified a number of other chromosomal loci as potentially linked to the development of iMAD. Among them, the chromosomal locus 5q13 containing the gene for a cAMP-specific PDE, PDE8B, was the second most favored by all analyses, including loss of heterozygosity and transmission disequilibrium testing 7 , supplementary data available at http://www.…”
Section: Introductionmentioning
confidence: 99%
“…7 -11 Adrenocortical hyperplasia in the presence of a partially inactivated PDE is likely to be caused by high cellular cAMP levels in a manner analogous to endocrine tumor formation in McCune -Albright syndrome. 7,12 The GWA study identified a number of other chromosomal loci as potentially linked to the development of iMAD. Among them, the chromosomal locus 5q13 containing the gene for a cAMP-specific PDE, PDE8B, was the second most favored by all analyses, including loss of heterozygosity and transmission disequilibrium testing 7 , supplementary data available at http://www.…”
Section: Introductionmentioning
confidence: 99%
“…The gene is located on band 20q13, an area that codes for the a subunit on G-protein receptors. 1,[10][11][12][13][14][15][16] This mutation is also present in various endocrine tumors as well as FD. The G-proteins begin a cascade that ultimately leads to activation of the enzyme adenylyl cyclase that produces cAMP.…”
Section: Clinical and Radiologic Presentationmentioning
confidence: 99%
“…In MAS, there is a missense mutation that causes the substitution of arginine in position 201 of the Gs-a gene. [11][12][13] Normally, there is an almost immediate deactivation of adenylyl cyclase and a break down of the cAMP. In MAS, that does not occur.…”
Section: Clinical and Radiologic Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…However only patient's affected organs carry a significant percentage of mutant cells and these tissues are not always available (4). A low percentage of mutated cells may be present in peripheral blood and could be used in the identification of GNAS-activating mutations leading to earlier diagnosis in patients with partial forms of MAS [8][9][10]. Nevertheless, this is only realistic if an accurate and sensitive assay for mosaic mutations detection is available.…”
Section: Introductionmentioning
confidence: 99%